2,6-Dimethyl-4-(4-Chlorophenyldiazenyl)phenol - Kocaokutgen, H.; Gür, M.; Soylu, S.; Lönnecke, P. (Int Union Crystallography, 2003)
The crystal structure of the title compound, C14H 13ClN2O, determined at 213 K, shows that the molecule is approximately planar in the solid state, having a trans configuration with respect to the azo double bond, as found for other diazene (azobenzene) derivatives. The dihedral angle between the planes of the two aromatic rings is 5.48 (10)°. Hydroxyl groups are linked to each other by intermolecular hydrogen bonds along the b axis. © 2003 International Union of Crystallography Printed in Great Britain - all rights reserved.